The Influence of Product Quality, Service Quality and Sharia Finance Knowledge on Saving Decision at Indonesia Sharia Bank In Makassar City - andi fadia faradina, andi fadia (Study of Scientific and Behavioral Management, 2024)
This study aims to analyze the effect of product quality, service quality, financial knowledge of Bank Syariah Indonesia on customers’ saving decisions at Bank Syariah Indonesia in Makassar City. This research is a correlational study, the data collection method used in this study is primary data, namely observation, and questionnaires. The population used in this study was 120 respondents. The data processing technique used is the data quality test, a classical assumption test. With the results of the research Pasrial Product Quality Plays a Role and Influences Saving Decisions at Bank Syariah Indonesia in Makassar City, Partially Service Quality Plays a Role and Influences Saving Decisions at Bank Syariah Indonesia in Makassar City, Partially Knowledge of Islamic Finance Plays a Role and Influencing Saving Decisions at Bank Syariah Indonesia in Makassar City and Simultaneously Product Quality Service Quality and Saving Knowledge Simultaneously Affects against the decision to save at Bank Syariah Indonesia in Makassar City. Keyword: Saving Decisions, Product Quality, Service Quality. Saving Knowledge